SOLUTION:
Step 1 :
In this question, we are told that a formula modeling how to add finite sums in an arithmetic sequence is represented by the equation:
[tex]S\text{ =}\frac{n}{2}(\text{ a + b )}[/tex]Step 2:
We are meant to express a in terms of b, s, and n.
Then, we have that:
[tex]\begin{gathered} S\text{ =}\frac{n}{2}\text{ ( a + b )} \\ \text{cross}-\text{ multiply, we have that:} \\ 2S\text{ = na + nb} \\ 2S\text{ - nb = na} \\ \text{Divide both sides by n, we have that:} \\ \frac{2S\text{ -nb}}{n}\text{ = a } \end{gathered}[/tex]CONCLUSION:
[tex]a\text{ = }\frac{2S\text{ - nb}}{n}[/tex]